The Work Environment as a Mediating Factor in the Effect of Selection and Recruitment on Employee Performance at PT. Persada Multi Mandiri - Latunreng, Wahyuddin; Hernawan, Eric (Institut Ilmu Sosial dan Manajemen STIAMI, 2023)
In order to ascertain the indirect impact of recruitment and choice on the performance of PT. Persada Multi Mandiri, this study uses the independent variable work environment as a mediator. This impact can be determined by determining the direct impact of several choices, recruitment, and work environment on the performance of PT employees. Persada Multi Mandiri and the impact of partial selection and adoption in the work environment. The results of this study were obtained from the results of a questionnaire of 50 samples from 85 members of the PT employee population . Persada Multi Mandiri . After the study data passes the validity, reliability, normalcy, multicollinearity, and heteroscedasticity tests, the simple linear regression and multiple linear regression calculations are made. Simple regression significance test was performed by t-test. While the multiple regression significance test was carried out using the F test. The results obtained from all direct and indirect effects were significant and positive. The percentage of influence of selection, recruitment, and work environment on PT employee performance is displayed separately . Persada Multi Mandiri is 44.0%, 41.2%. and 20.7%. The direct impact of selection and recruitment on the work environment is 31.7% and 36.1%, while the impact of selection, recruitment and work environment on PT performance is 31.7% and 36.1% . Persada Multi Mandiri by 44.3%.